(untitled) (Journal of Economic Research & Business Administration, 2015)
Article named after «Gnoseological aspects of institutional specifi cs of economic subjectivity of the modern state» it is devoted to identifi cation of a trajectory of state’s institutional genesis. In the article locates the dialectic interrelation between the political and economic parties of the state, being shown in that specifi c of the state as the special economic subject is defi ned by its directivity as political and legal institute. The analysis in work shows that an economic institutionalization of the state is dualistically: its subject component consists in a social and institutional form of personifi cation of society as agent of relations of production; functional features are defi ned by system nature of participation at all stages of reproduction process by realization of productive, investment, transfer, transactional and consumer impulses.